2021
DOI: 10.21203/rs.3.rs-788944/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the epidemiology of out-of-hospital cardiac arrest: A systematic review and meta-analysis

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has significantly influenced epidemiology, yet its impact on out-of-hospital cardiac arrest (OHCA) remains unclear. We aimed to evaluate the impact of the pandemic on the incidence and case fatality rate (CFR) of OHCA. We also evaluated the impact on intermediate outcomes and clinical characteristics. Methods PubMed, EMBASE, Web of Science, Scopus, and Cochrane Library databases were searched from inception to May 3, 2021. Studies were included if t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In this study conducted on patients with OHCA in Seoul, the number of TOR cases confirmed by EMS paramedics increased during the COVID-19 pandemic, and those due to decisions by medical directors and refusal of CPR by family members significantly increased. These results are consistent with those of previous studies reporting a rise in OHCAs occurring at home and an increase in TOR at the scene due to strengthened social distancing and a decrease in patients' use of medical institutions during the COVID-19 pandemic [15][16][17]. In an observational study using an OHCA registry in the United States, Chan et al [18] found that, in regions with high COVID-19 mortality rates, the number of on-site resuscitation termination cases was more likely to be increased; however, even in areas with relatively low COVID-19 mortality rates, the number of on-site resuscitation termination cases significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…In this study conducted on patients with OHCA in Seoul, the number of TOR cases confirmed by EMS paramedics increased during the COVID-19 pandemic, and those due to decisions by medical directors and refusal of CPR by family members significantly increased. These results are consistent with those of previous studies reporting a rise in OHCAs occurring at home and an increase in TOR at the scene due to strengthened social distancing and a decrease in patients' use of medical institutions during the COVID-19 pandemic [15][16][17]. In an observational study using an OHCA registry in the United States, Chan et al [18] found that, in regions with high COVID-19 mortality rates, the number of on-site resuscitation termination cases was more likely to be increased; however, even in areas with relatively low COVID-19 mortality rates, the number of on-site resuscitation termination cases significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…Second, we have not further stratified the patient’s clinical status before PCI. Third, an increase in out-of-hospital cardiac arrest and death was reported in some countries during the early COVID-19 epidemic, [27,28] and this may affect our study results. However, due to the limitation of the data, we could not analyze this in the study.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in many areas, an increase in unwitnessed OHCA was highlighted [7 ▪ ,8 ▪ ,20], probably due to the fact that many people spent the quarantine in different rooms or houses than their relatives. The spectrum of etiologies of OHCA has also been influenced by the pandemic, with an increase of medical etiology [7 ▪ ,9 ▪ ,36], especially in those regions who experienced an increase in OHCA. Similarly, in these areas, the rate of OHCA with a shockable presenting rhythm decreased in favor of not-shockable ones [7 ▪ ,8 ▪ ,11 ▪ ,13,36].…”
Section: Changing In Out-of-hospital Cardiac Arrest Patients’ Charact...mentioning
confidence: 99%
“…The spectrum of etiologies of OHCA has also been influenced by the pandemic, with an increase of medical etiology [7 ▪ ,9 ▪ ,36], especially in those regions who experienced an increase in OHCA. Similarly, in these areas, the rate of OHCA with a shockable presenting rhythm decreased in favor of not-shockable ones [7 ▪ ,8 ▪ ,11 ▪ ,13,36]. Both these changes may be explained considering that many of the exceeding OHCA in 2020 were due to COVID-19 [6 ▪ ].…”
Section: Changing In Out-of-hospital Cardiac Arrest Patients’ Charact...mentioning
confidence: 99%
See 1 more Smart Citation